High prevalence of obesity, central obesity and abnormal glucose tolerance in the middle-aged Finnish population - Vanhala Mauno; Saltevo Juha T; Puolijoki Hannu; Oksa Heikki; Korpi-Hyövälti Eeva; Barengo Noël C; Saaristo Timo E; Sundvall Jouko; Saarikoski Liisa; Peltonen Markku; Tuomilehto Jaakko (BMC, 2008)
Abstract Background There is a worldwide increase in the prevalence of obesity and disturbances in glucose metabolism. The aim of this study was to assess the current prevalence of obesity, central obesity and abnormal glucose tolerance in Finnish population, and to investigate the associations between body mass index (BMI), waist circumference and abnormal glucose tolerance. Methods A cross-sectional population-based survey was conducted in Finland during October 2004 and January 2005. A total of 4500 randomly selected individuals aged 45-74 years were invited to a health examination that included an oral glucose tolerance test. The participation rate was 62% in men and 67% in women. Results The prevalence of obesity was 23.5% (95% Confidence Interval (CI) 21.1-25.9) in men, and 28.0% (95% CI 25.5-30.5) in women. The overall prevalence of abnormal glucose tolerance (including type 2 diabetes, impaired glucose tolerance, or impaired fasting glucose) was 42.0% (95% CI 39.2-44.8) in men and 33.4% (95% CI 30.9-36.0) in women. The prevalence of previously unknown, screen-detected type 2 diabetes was 9.3% (95% CI 7.7-11.0) in men and 7.3% (95% CI 5.9-8.7) in women. Central obesity was associated with abnormal glucose tolerance within each of the three BMI categories normal (< 25 kg/m2), overweight (25-29 kg/m2), and obese (≥ 30 kg/m2). Conclusion In a population-based random sample of Finnish population, prevalences of obesity, central obesity and abnormal glucose tolerance were found to be high. A remarkably high number of previously undetected cases of type 2 diabetes was detected. Waist circumference is a predictor of abnormal glucose tolerance in all categories of obesity.